Predicting and benchmarking human protein complexes - Sng, Jonathan Zan Jie. (2012)
Yeast is currently a model organism where many methods have been proposed for protein complexes. Benchmark complexes are also collected for evaluation of existing complex detection methods. However, the studies on human protein complexes are rather limited. This project has three main tasks. First, it is to collect known human protein complexes from existing databases and literature, for example, CUROM. Second, we can apply existing methods that are proposed for detecting yeast protein complexes to detect human protein complexes from human protein-protein interaction data. Third, we will evaluate our predicted complexes based on our collected benchmark complexes.